Der griechische Schlachtfeldgott Ἐνῡάλιος - Schaffner, Stefan (Historische Sprachforschung, 2019)
The Greek theonym Ἐνῡάλιος (cf. Mycenaean E-nu-wa-ri-jo /Enūalios/ and West Argolian Ἐνυϝαλιος VIIa), a god of war beside Ἄρης, is usually deemed a substrate word of pre-Greek origin (cf. e.g. Frisk I, 536). In the language of Homeros, only Ἐνῡάλιος is combined with the epithet ἀνδρϵϊφόντης 'man-slaying' in the formula Ἐνῡαλίῳ ἀνδρϵϊφόντῃ (Il. 2.651, 7.166, 8.264, 17.25) at the end of the hexameter. As this formula matches a metrically correct hexameter ending only in its pre-Proto-Greek form ∗enūalíō (h2)ankwh(gwh)óntā (with still existing-sonans of the epithet), it can be concluded, that the formula itself must have been created and the single elements of the formula must already have existed at an astonishingly early period of the Greek language history (before ca. 2000 BC). These facts speak against the recently made assumption that the Greek god of war Ἐνῡάλιος was borrowed from the hapax legomenon Lydian ẽnwaλa- (LW 22 § 6a) or a western Anatolian preform of ẽnwaλa- 'lord, master' (cf. Ἐνῡαλίοιο ἄνακτος 'of (the) lord Enyalios' Archilochus Fr. 1 D). However, the proposed meaning 'lord, master' of the hapax legomenon Lydian ẽnwaλa- is to far away to be secured. In this paper, it is argued that the Greek theonym Ἐνῡάλιος (cf. Mycenaean E-nu-wa-ri-jo /Enūalios/, West Argolian Ἐνυϝαλιος) < Proto-Greek ∗enūálio-s (with ū due to metrical lengthening) can etymologically be interpreted as a continuant of a prepositional governing compound pre-Proto-Greek ∗(h1)enu-l̥h3- io-s 'who is along the battlefield, who acts along the battlefield' (perhaps an original epithet of Ἄρης, becoming then an independent god of war). The preverb of this compound can be identified with the adverb PIE ∗(h1)énu 'along, after' (cf. Vedic ánu 'along, after, furthermore, later', Young Avestaan anu 'after, according to', Old Persian anuv 'after, according to' etc.). Within Greek, the second element ∗-l̥h3-io- (with the compositional suffix ∗-io-, cf. e.g. Greek ἐπι-δήμιος : δῆμος) can etymologically be connected with the (passive) η-aorist ἁλῶναι 'to die, to fall, to be killed (in battle, in war)' < ∗l̥h3-eh1- to the PIE root ∗elh3- 'to defeat, to slay, to beat to death sb. (in battle, in war)'. Outside Greek, the proposed meaning 'battlefield' of the second element ∗-l̥h3-io- matches well Proto-Germanic ∗ala- m./n. 'battlefield, battle' (Old Norse valr m., Old English wæl n., Old High German wal m., Middle Dutch wale-stat) < PIE ∗ólh3-o- m. 'killing, slaying (in battle, in war)' and Proto-Germanic ∗ala- m. 'the slain (on battlefield)' (Old Norse valr m., Old English wæl n.) < PIE ∗olh3-ó-'the slain, the killed (on battlefield)' Thus, the proposed etymology of Ἐνῡάλιος provides a fitting and suitable motive of denomination for a god of war (or, if so, for an original epithet of a god of war).
CRIS-Team Scopus Importer:2024-12-16